2009
DOI: 10.1158/1055-9965.epi-08-0715
|View full text |Cite
|
Sign up to set email alerts
|

Nipple Aspirate Fluid Collection, Related Factors and Relationship between Carcinoembryonic Antigen in Nipple Aspirate Fluid and Breast Diseases in Women in Harbin, PRC

Abstract: This study aimed to examine the factors related to the ability to obtain nipple aspirate fluids in Chinese women and to evaluate the diagnostic value of carcinoembryonic antigen (CEA) in nipple aspiration fluids. Cross-sectional and case-control studies were used to examine the factors associated with the ability to obtain nipple aspiration fluids. A matched casecontrol study was used to explore the association of CEA level in nipple aspiration fluids with breast disease. CEA level was log 10 -transformed to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Also, the women served as their own controls and, therefore, temporal improvements in NAF production or collection cannot be excluded. Our study also agrees with previous reports that fewer Asian than Caucasian women are able to produce NAF (11,27,28).…”
Section: Discussionsupporting
confidence: 93%
“…Also, the women served as their own controls and, therefore, temporal improvements in NAF production or collection cannot be excluded. Our study also agrees with previous reports that fewer Asian than Caucasian women are able to produce NAF (11,27,28).…”
Section: Discussionsupporting
confidence: 93%
“…There is a paucity of reports that have examined the diagnostic values of the three abovementioned tumor markers for breast lesions with nipple discharge [ 16 , 32 , 33 ]. A literature search revealed that there are no references for the levels of these markers in milk.…”
Section: Discussionmentioning
confidence: 99%
“…To maintain stable physiology of the breast, an equilibrium exists between fluid secretion and re-absorption. Several factors are associated with NAF production; age, ethnicity, early menarche, history of lactation, high dietary fat consumption and dietary intake of lactose [ 80 ]. There is also a direct relationship between ear wax and NAF because both are produced by modified apocrine glands (ceruminous and mammary, respectively).…”
Section: Nipple Aspirate Fluid (Naf)mentioning
confidence: 99%
“…Women with wet ear wax yield more NAF, compared to women with dry ear wax [ 81 ]. Premenopausal women with lactation experience, aged 30–50 years and who had early onset of menarche produce more NAF compared to those who have not had children [ 80 ]. A study of 25 to 49-year-old premenopausal nulliparous women found that proportionately, Asian-descendant women were less likely to produce NAF compared to White American women [ 53 ].…”
Section: Nipple Aspirate Fluid (Naf)mentioning
confidence: 99%